Chemotherapy-induced peripheral neuropathy clinical trials: Review and recommendations. (22nd August 2017) - Gewandter, Jennifer S.; Freeman, Roy; Kitt, Rachel A.; Cavaletti, Guido; Gauthier, Lynn R.; McDermott, Michael P.; Mohile, Nimish A.; Mohlie, Supriya G.; Smith, A. Gordon; Tejani, Mohamedtaki A.; Turk, Dennis C.; Dworkin, Robert H.
Abstract : Objective: To assess the design characteristics and reporting quality of published randomized controlled trials (RCTs) for treatments of chemotherapy-induced peripheral neuropathy (CIPN) initiated before or during chemotherapy. Methods: In this systematic review of RCTs of preventive or symptomatic pharmacologic treatments for CIPN initiated before or during chemotherapy treatment, articles were identified by updating the PubMed search utilized in the CIPN treatment guidelines published in the Journal of Clinical Oncology in 2014. Results: Thirty-eight articles were identified. The majority included only patients receiving platinum therapies (61%) and used a placebo control (79%). Common exclusion criteria were preexisting neuropathy (84%), diabetes (55%), and receiving treatments that could potentially improve neuropathy symptoms (45%). Ninety-five percent of studies initiated the experimental treatment before CIPN symptoms occurred. Although 58% of articles identified a primary outcome measure (POM), only 32% specified a primary analysis. Approximately half (54%) of the POMs were patient-reported outcome measures of symptoms and functional impairment. Other POMs included composite measures of symptoms and clinician-rated signs (23%) and vibration tests (14%). Only 32% of articles indicated how data from participants who prematurely discontinued chemotherapy were analyzed, and 21% and 29% reported the number of participants who discontinued chemotherapy due to neuropathy or other/unspecified reasons, respectively. Conclusions: These data identify reporting practices that could be improved in order to enhance readers' ability to critically evaluate RCTs of CIPN treatments and use the findings to inform the design of future studies and clinical practice. Reporting recommendations are provided.